Поиск драйверов развития страхования жизни в России - Лапухина, Виктория Геннадьевна (Перспективы развития фундаментальных наук. Т. 5 : сборник научных трудов XVIII Международной конференции студентов, аспирантов и молодых ученых, 27–30 апреля 2021 г.)
Life insurance is a source of long-term money formation in the economy and a way of financial protection of people. In this study, we consider the current situation, identify the problems and drivers of the development of life insurance in Russia.